Recent Researches and Technologies on Software Reliability Evaluation - Li, Yingchun; Gao, Kaiye; Peng, Rui (Recent Patents on Engineering, 2021)
Background: With the rapid development of computer and Internet technologies, the measurement of software reliability has become a key point. Software reliability modeling is an important way to measure software reliability. However, there are many disadvantages in the classic model. Therefore, this paper reviews current researches in software reliability and discusses ways to improve the model from a new perspective. Objective: This paper reviews the current researches on software reliability, analyzes the existing patented technology, and points out some future directions to improve the current models to provide a more accurate and efficient way for software reliability measurement. Methods: This study introduces the general methods of software reliability evaluation, analyzes the disadvantages of these methods in practical application, draws lessons from the patent, and puts forward some new ideas to solve the problems. Results: Disadvantages of current researches are identified based on literature review. In addition, two suggestions are given to improve the current models. Conclusion: Although the software reliability has made great progress, there are still many things to be studied in the future. The problems of software reliability in real life should be gradually solved.
Keywords: software reliability model